Tight junction proteins in glial tumors development and progression - Moskal, Jakub; Michalak, Slawomir (Frontiers in Cellular Neuroscience, 2025)
Tight junctions form a paracellular barrier in epithelial and endothelial cells, and they regulate the diffusion of fluids, molecules, and the penetration of cells across tissue compartments. Tight junctions are composed of a group of integral membrane proteins, which include the claudin family, tight junction-associated Marvel protein family, junctional adhesion molecule family, and proteins that anchor the cytoskeleton, such as zonula occludens proteins and the cingulin family. Several factors, such as neurotransmitters or cytokines, and processes like ischemia/hypoxia, inflammation, tumorigenesis, phosphorylation/dephosphorylation, ubiquitination, and palmitoylation, regulate tight junction proteins. Claudins are involved in tumorigenesis processes that lead to glioma formation. In gliomas, there is a noticeable dysregulation of claudins, occludin, and zonula occludens-1 abundance, and their dislocation has been observed. The weakening of intercellular adhesion and cell detachment is responsible for glioma infiltration into surrounding tissues. Furthermore, the paracellular permeability of the blood–brain barrier, formed with the involvement of tight junction proteins, influences the development of peritumoral edema – and, simultaneously, the rate of drug delivery to the glial tumor. Understanding the junctional and paracellular environments in brain tumors is crucial to predicting glial tumor progression and the feasibility of chemotherapeutic drug delivery. This knowledge may also illuminate differences between high and low-grade gliomas.